Contribution of the organic law of territorial planning to the tourism management in Colombia (REVISTA NODO, 2021)
The Organic Law of Territorial Planning (Law 1454, 2011) defines a general framework which considers the Territorial Planning as an instrument planning and management to promote capacity for decentralization, planning, management and administration of their own interests in the entities territorial and regional integration organizations proposals. This document aims to articulate this Law with national regulations and guidelines issued by organizations dedicated to the study and management of tourism at global and national level, in order to serve as a support in shaping regional strategies for managing destinations tourist sustainable and competitive, concluding the powers in tourism indicate the regulations and associated instruments in order to comply with the Constitution in the consolidation of a ““social state of law, organized as a unitary republic, decentralized, with autonomous territorial units, democratic, participatory and pluralistic “.
Keywords: Regional development; Tourism; Legal systems; Colombia